2015
DOI: 10.1007/s13369-015-1694-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Extraction Duration on the Chemical Composition and Biological Activities of Essential Oil of Thymus pallescens de Noé

Abstract: Thymus pallescens de Noé essential oils were isolated from the plant's dried leaves, by hydrodistillation, with different distillation times (30 min, 1, 2 and 3 h). The essential oils compositions and their antioxidant, antimicrobial and insecticidal activities were examined. The chemical compositions of the oils were determined by GC and GC-MS. The antioxidant capacity was tested by four complementary methods: thiobarbituric acid reactive substances, ferric reducing power and scavenging of radicals DPPH • (2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…The chemical compositions of the EOs were analyzed by GC-MS, which resulted in the identification and quantification of more than 30 compounds. Our analysis showed that carvacrol (67.2%), p-cymene (16.2%), and thymol (4.9%) were the major components of T. pallescens EO, which agrees with previous studies (Benchabane et al 2015;Moutassem et al 2019). The major volatile constituents of C. citratus EO were identified as geraniol (20.8%) and limonene (10.5%), which are similar to those identified in previous studies conducted on the same species, with only slight differences (Bassolé et al 2011;Moutassem et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The chemical compositions of the EOs were analyzed by GC-MS, which resulted in the identification and quantification of more than 30 compounds. Our analysis showed that carvacrol (67.2%), p-cymene (16.2%), and thymol (4.9%) were the major components of T. pallescens EO, which agrees with previous studies (Benchabane et al 2015;Moutassem et al 2019). The major volatile constituents of C. citratus EO were identified as geraniol (20.8%) and limonene (10.5%), which are similar to those identified in previous studies conducted on the same species, with only slight differences (Bassolé et al 2011;Moutassem et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Benchabane et al and Jarić et al described similar findings in Thymus -tested samples. The authors concluded that thymol and carvacrol were not present in tested Thymus species cultivated in Lithuania, Estonia and Spain [ 23 , 24 ]. In another study, myrcene was reported in Thymus serpyllum L. up to 74.2% of the total determined volatile compounds, depending on the volatile oil extraction technique [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EOt was obtained by hydrodistillation [27]. Briefly, fresh-cut plant was hydrodistilled using a Clevenger-type apparatus (100 g• L −1 water) for 4 h. The oil was collected and kept at 4 • C until use.…”
Section: B Essential Oil Extractionmentioning
confidence: 99%
“…Absorbances of these solutions were measured at 517 nm (Epoch Microplate Spectrophotometer, Biotek, USA). On the other hand, the ABTS + method [27] is based on the reduction of the green ABTS + radical cation. A volume of 25 μL of each solution (NC-EOt, EOt or carvacrol, at a concentration of 1000 μg• mL −1 ) was added to 1 mL of ABTS + methanol solution (7 mM).…”
Section: F Antioxidant Activitymentioning
confidence: 99%